Perbedaan Individu dalam Proses Pembelajaran - Dalila Turhusna; Saomi Solatun (AS-SABIQUN, 2020)
In the learning process, the teacher is not enough just to deliver the material or what is commonly referred to as the transfer of knowledge. Because in learning there are several aspects of assessment that must be done by the teacher to students, namely cognitive aspects, affective aspects, and psychomotor aspects. Therefore, for the realization of learning objectives with optimal results, the teacher needs to recognize the characteristics of each student. We will find that individual variations are usually the result of interactions between hereditary and environmental influences simultaneously, which ultimately results in a unique human being. Therefore as a teacher should be able to understand the characteristics and properties of each individual or student. Specific ways and methods and apply them directly in learning so that they know the differences of their students and how to overcome them in ways that are easily captured or understood by students.